TRANSFORMATION OF EDUCATION BASED ON COMPASSION THROUGH THE DEVELOPMENT OF A CURRICULUM OF LOVE AS AN EFFORT TO CREATE AN INCLUSIVE, CIVILISED, AND CONSCIENTIOUS LEARNING ECOSYSTEM: A THEORETICAL AND EMPIRICAL LITERATURE REVIEW - Abdul Wahab Syakhrani (Adisam Publisher, 2025)
This study examines the transformation of education based on the value of compassion through the development of the Love Curriculum as an effort to create an inclusive, civilised, and conscientious learning ecosystem. The study was conducted theoretically and empirically using a literature review approach, integrating humanistic education theory, caring pedagogy, and character education in the context of the national curriculum. The results of the theoretical study confirm that the Love Curriculum prioritises the value of love as the foundation of holistic learning, focusing not only on cognitive aspects but also on affective and spiritual aspects. Empirical evidence shows that this curriculum is effective in increasing learning motivation, emotional intelligence, positive social behaviour, and reducing conflict and discrimination in the school environment. The Love-Based Curriculum has been proven to support the development of an inclusive and civilised character, which is the main asset towards a harmonious and civilised society. This study recommends strengthening cross-stakeholder collaboration in the implementation of the Love Curriculum so that it can become a strategy for sustainable national education transformation.